Crucial surviving aspects for vitrified in vitro-produced bovine embryos - Sudano, Mateus Jose [UNESP]; Paschoal, Daniela Martins [UNESP]; Silva Rascado, Tatiana da [UNESP]; Crocomo, Leticia Ferrari [UNESP]; Ona Magalhaes, Luis Carlos [UNESP]; Martins Junior, Alicio [UNESP]; Machado, Rui; Cruz Landim-Alvarenga, Fernanda da [UNESP] (Cambridge University Press, 2014)
The objective of the present study was to correlate some parameters (cleavage, blastocyst production, quality degree score, total cell number, fresh apoptosis and lipid content) with embryo survival after cryopreservation. A total of 1727 in vitro-produced bovine blastocysts were used to establish the parameters (mean +/- standard error of the mean (SEM)) for cleavage (85.6 +/- 0.8), blastocyst production (39.9 +/- 1.4), quality degree score (1.6 +/- 0.1), total cell number (140.1 +/- 2.9), fresh apoptosis (20.8 +/- 1.1) and lipid content (21.3 +/- 0.8 droplets). On the same way 1316 blastocysts were vitrified for the determination of post-cryopreservation embryo survival (49.4 +/- 1.9). Fresh apoptosis rate and total lipid droplets value were correlated (P < 0.05) with embryo survival after cryopreservation (r = 0.91 and r = 0.59; respectively). However, cleavage, blastocyst production, quality degree score and total cell number were not correlated (P > 0.05) with embryo cryotolerance (r = 0.23, r = 0.38, r = 0.22 and r = 0.28; respectively). Therefore, the increased lipid content was moderately correlated with apoptosis in vitrified blastocysts. On the other hand, increased apoptosis in fresh blastocysts was strongly correlated with apoptosis in vitrified blastocysts, which indicated that the apoptosis rate in fresh embryos was a better parameter than the lipid content to predict post-vitrification embryo survival.
Keywords: Cryotolerance; Lipid content; Embryo quality; Apoptosis; Vitrification